1999
DOI: 10.1103/physreve.60.6852
|View full text |Cite
|
Sign up to set email alerts
|

Photonic defect modes of cholesteric liquid crystals

Abstract: We investigate defect modes of cholesteric liquid crystals as photonic band gap materials. For normal incidence of light, cholesteric liquid crystals exhibit total reflection for the circular polarization with the same handedness as that of cholesteric helix. However, the other orthogonal component is completely transmitted. When we replace a thin layer of liquid crystal by an isotropic material as a defect, defect modes are induced for both polarizations of incident light. We analyze the wavelength and reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
95
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(98 citation statements)
references
References 13 publications
2
95
1
Order By: Relevance
“…However, the proper understanding some of its basic features has appeared much later, when the interest in lasing in LC systems has been renovated [2][3][4][5][6][7][8][9][10][11]. The current interpretation of the effect is based on the photonic band-gap concept [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the proper understanding some of its basic features has appeared much later, when the interest in lasing in LC systems has been renovated [2][3][4][5][6][7][8][9][10][11]. The current interpretation of the effect is based on the photonic band-gap concept [2].…”
Section: Introductionmentioning
confidence: 99%
“…Because the density of photon states achieves maxima just at the spectral boundaries of the band, namely these spectral regions are treated as most favourable for appearance of the low-threshold lasing effect. The lasing inside the photonic band-gap is forbidden unless defects are introduced into CLC layers [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It was in dyedoped CLCs that suppression of the density of states in a stop band and lasing in long-lived modes at the band edge were first demonstrated [10]. In analogy with isotropic periodic structures, a defect can be produced in a helical structure by adding an isotropic layer in the middle of a CLC [11,12]. The reflection and transmission of radiation with opposite senses of circular polarization were shown to be equal at resonance [12].…”
mentioning
confidence: 99%
“…In analogy with isotropic periodic structures, a defect can be produced in a helical structure by adding an isotropic layer in the middle of a CLC [11,12]. The reflection and transmission of radiation with opposite senses of circular polarization were shown to be equal at resonance [12]. In addition, a "chiral twist" defect created by rotating one part of the sample about its helical axis without separating the two parts was proposed (Fig.…”
mentioning
confidence: 99%
“…The use of defect modes has also been proposed for lasing at low threshold [12,13]. Generally, two kinds of configurations for generating defect modes in CLCs are suggested theoretically: introduction of an isotropic spacing layer in the middle of CLCs [14] and creation of a phase jump without any spacing in CLC structures [15 -17]. Recently, Schmidtke et al [18] experimentally demonstrated the defect mode lasing caused by a phase jump in CLCs and described its polarization characteristics.…”
Section: Introductionmentioning
confidence: 99%